Hubungan Persepsi Guru terhadap Kurikulum Merdeka dengan Implementasi Pembelajaran Tematik: Studi Chi-Square - Susiandri; Habibi, Mhmd (Journal of Practice Learning and Educational Development, 2026)
The Merdeka Curriculum is designed to provide flexibility for teachers in designing and implementing student-centered learning, including the implementation of thematic learning in elementary schools. However, the success of curriculum implementation is greatly influenced by teachers' perceptions of the policy. This study aims to determine the relationship between teachers' perceptions of the Merdeka Curriculum and the implementation of thematic learning in elementary schools. This study used a quantitative approach with a correlational design. The data analysis technique used was the Chi-Square test to see the relationship between two categorical variables. Data were collected through a teacher perception questionnaire and a thematic learning implementation observation sheet. The results showed a significant relationship between teachers' perceptions of the Merdeka Curriculum and the implementation of thematic learning. These findings indicate that positive teacher perceptions contribute to more optimal thematic learning implementation. Therefore, strengthening teachers' understanding and positive attitudes towards the Merdeka Curriculum is an important factor in its successful implementation in elementary schools.